2002
DOI: 10.1128/jcm.40.11.4068-4071.2002
|View full text |Cite
|
Sign up to set email alerts
|

Occult Hepatitis B Virus Infection and Clinical Outcomes of Patients with Chronic Hepatitis C

Abstract: Although occult hepatitis B virus (HBV) infections in individuals without detectable hepatitis B surfaceantigen (HBsAg) may occur and have been reported to be common in patients with chronic hepatitis C, the clinical relevance remains controversial. We searched for serum HBV DNA in 210 HBsAg-negative patients with hepatitis C virus (HCV)-related liver disease (110 patients with chronic hepatitis, 50 patients with cirrhosis, and 50 patients with hepatocellular carcinoma) by PCR. Most of the patients had detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
3
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 22 publications
10
145
3
5
Order By: Relevance
“…The prevalence of occult B infection in HCV-infected patients in the present study (19.5%) was above the one reported by some authors (9,12) and below the percentages reported by others (21,28,36,38) , which can be as high as 76% (24) . It should be highlighted that the latter studies used PCR for viral DNA detection, a technique which is more sensitive than immunohistochemistry (4,12) .…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…The prevalence of occult B infection in HCV-infected patients in the present study (19.5%) was above the one reported by some authors (9,12) and below the percentages reported by others (21,28,36,38) , which can be as high as 76% (24) . It should be highlighted that the latter studies used PCR for viral DNA detection, a technique which is more sensitive than immunohistochemistry (4,12) .…”
Section: Discussioncontrasting
confidence: 36%
“…In contrast, HBV DNA has been found in serum by PCR in 6.7% to 52% (13,15,16) of HBsAg-negative patients with chronic HCV infection, in 5% to 76% (7,10,30) of patients with chronic liver disease of no defi ned etiology, and in 0% (15) to 15% (21) of healthy donors.…”
Section: Discussionmentioning
confidence: 96%
“…Zen (2007) found that ABCG gene was scattered or focally clustered in HCC. The overexpression of ABCG2 gene in the Egyptian HCC cases clarified the Akt high expression levels described in similar cases studied by our group (Kao et al, 2002).…”
Section: Discussionmentioning
confidence: 73%
“…DNA was extracted from frozen liver tissues according to standard protocol and was analyzed for HBV genomes with polymerase chain reaction (PCR) assays to detect the S, X and core genes as previously described (Kao et al, 2002) to exclude occult HBV infection.…”
Section: Detection Of Occult Hbv Dnamentioning
confidence: 99%
“…Infections with hepatitis B virus (HBV) represent a significant cause of morbidity and mortality worldwide and constitute a problem of global public health importance 1 .…”
Section: Introductionmentioning
confidence: 99%